Oral presentation errors of diploma students in an integrated language skills course - Azmi, Azzieatul Syazwanie (2016)
This paper analyses grammatical errors in English oral presentation made by the students in Integrated Language Skills (ELC120) course. The specific objective of the study was to determine the types of grammatical errors based on Dulay, Burt and Krashen’s (1982) surface structure taxonomy, namely, misformation, omission, addition, and misordering. The data also was categorised into linguistic taxonomy of error analysis by James (1998) (cited in Ellis and Barkhuizen, 2005). In order to attain the objectives of the study, case study was used which involves the use of mixed data collection which are quantitative and qualitative data collection methods. 60 students were involved as sample of this study. In addition, students’ oral presentation and interviews were used as data to explore grammatical errors made by Integrated Language Skills (ELC120) students. The findings of the study reveal that the most frequent error committed by the students was the improper use of English verbs. Besides, it can be inferred from the result of this study that the responses of the students are consistent with previous literature on error analysis. The analysis generated a conclusion that the lacks of knowledge on grammar and interlanguage interference are the main factors of errors in students' oral presentation. In light of the findings, several recommendations and pedagogical implications were suggested in order to help ESL teachers in their attempt to reduce the difficulties in oral presentation among English students.